Relationship between parental physical activity and adolescents’ exercise cognition: the mediating role of family activity support - Liang, Fusheng; Yu, Huasen; Li, Feifei; Li, Xingying (Frontiers in Public Health, 2025)
BackgroundAdolescents’ exercise cognition influences their healthy development. While parental physical activity (PA) is linked to Adolescents’ exercise cognition, the role of family activity support in this relationship is still unclear. This study aims to examine how family activity support influences the relationship between parental PA and adolescents’ exercise cognition.MethodsA 2023 survey conducted across 15 provinces in China ultimately included 12,457 participants. Multiple linear regression examined the links between parental PA, family activity support, and adolescents’ exercise cognition, adjusting for potential confounders. A mediation model tested whether family activity support mediated the relationship between parental PA and adolescents’ exercise cognition. Subgroup analyses explored heterogeneity across groups.ResultsAfter adjusting for confounding variables, parental PA was positively associated with adolescents’ exercise cognition (β = 9.47 × 10−2, 95% CI: 8 × 10−4 to 1.1 × 10−3; p < 0.001). Family activity support was also positively associated with adolescents’ exercise cognition (β = 47.86 × 10−2, 95% CI: 1.045–1.118; p < 0.001). Family activity support mediated 49.05% of the total association of parental PA on adolescents’ exercise cognition, with a mediation effect size of 4.65 × 10−2, suggesting that higher parental PA was indirectly linked to improved adolescents’ exercise cognition through increased family activity support.ConclusionThe study found that both parental PA and family activity support were positively associated with adolescents’ exercise cognition, and family activity support mediated the relationship between parental PA and adolescents’ exercise cognition.